Two strategies for HIV-specific recombinase library evolution through structure optimizing - Song, Lingbo. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisors: Andrew Bohm, and James Baleja.; Keywords: Pharmacology, Bioengineering, and Biomedical engineering.